Mangiferin Relieves Lipopolysaccharide-Induced Injury by Up-Regulating miR-181a via Targeting PTEN in ATDC5 Cells - Ma, Yunfei; Liu, Ying; Ma, Yunyan; Jiang, Nan; Wang, Lei; Wang, Bowei; Niu, Wanting; Hu, Yanjun; Lin, Qingrong; Yu, Bin (Frontiers in Pharmacology, 2020)
Background: Mangiferin (MF) was reported to possess anti-inflammatory activity. This investigation tried to probe into the underlying mechanism of MF in osteoarthritis. Methods: ATDC5 cells were pretreated with series concentrations of MF (0.1, 1, 5, 10, 15, 20 μM) for 2 h and then were exposed to LPS (5 μg/ml) for 12 h to construct the inflammatory injury model. The cell viability, productions of pro-inflammatory cytokines and enzymes were respectively measured by employing CCK-8 assay, western blot, ELISA and qRT-PCR. miR-181a expression was altered by employing cell transfection. DCFH-DA method was employed for detecting ROS generation. Dual luciferase activity assay was conducted for analyzing the relationship between miR-181a and PTEN. The potential mechanism was determined by employing western blot. Results: High doses of MF treatment (15 and 20 μM) noticeably induced inflammatory injury exhibiting as increased the productions of pro-inflammatory cytokines, enzymes and ROS, activated NF-κB pathway and deactivated PTEN/PI3K/AKT pathway in ATDC5 cells. Besides, MF treatment notably remitted LPS-induced inflammatory injury through deactivation of NF-κB pathway and activation of PTEN/PI3K/AKT pathway. PTEN was a target of miR-181a. Inhibition of miR-181a remarkably reversed MF-triggered impacts on ATDC5 cells. Conclusion: MF attenuated LPS-induced inflammatory damage through miR-181a/PTEN axis and thereby inhibiting NF-κB pathway and activating PI3K/AKT pathway.